34‐6: Invited Paper: High Image Quality of 8K TV LCDs with Negative LC. Issue 1 (28th June 2022) - Chen, Dongchuan; Huang, Jianhua; Shao, Xibin; Liao, Yanping; Wang, Zhangtao; Lee, Seungmin; Zhan, Hongming; Guo, Yuanhui; Guo, Lei; Jiang, Liangliang; Lin, Lifeng; Qu, Yingying; et al.
Abstract : ADS display mode with positive LC mixture has been widely used in TV and other large size LCD products. After years of technical iterations, positive LC mixture have approached the material limit in terms of transmittance, contrast ratio and so on. In order to improve image quality continuously, especially for high end 8K TV products, we have developed a total negative LC (N‐LC) solution with rubbing alignment process. This total solution includes high CR negative LC material, rubbing PI material and process, and high‐transparent pixel ITO design. Based on this total solutions, TR has been increased by 30% for 8K LCDs. CR has been increased from 1400 to 2500:1 for 8K and 3000:1 for 4K LCDs. Meanwhile, this solution keep response time (RT) and reliability of image sticking (I/S) can meet the regular specifications.